2022
DOI: 10.3390/molecules27196345
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Transition in Low Molecular Weight Substances: The Example of the Silybin Flavonoid

Abstract: Silybin is a complex organic molecule with high bioactivity, extracted from the plant Silybum. As a pharmaceutical substance, silybin’s bioactivity has drawn considerable attention, while its other properties, e.g., thermodynamic properties and thermal stability, have been less studied. Silybin has been reported to exhibit a melting point, and values for its heat of fusion have been provided. In this work, differential scanning calorimetry, thermogravimetry including derivative thermogravimetry, infrared spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…In this temperature range, the mass loss of quercetin dihydrate was 7–8 wt.%, and at 130 °C fluidization occurred [ 12 ]. This behavior is pretty similar to the one that has been reported recently for silybin [ 14 ], thus, this effect in quercetin dihydrate seems to be a thermochemical transition. The quercetin used in the current study is not the dihydrate form and exhibits a much lower mass loss (0.9 ± 0.3 wt.%) around 100 °C (these values were calculated from three independent repetitions of the TGA measurements).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In this temperature range, the mass loss of quercetin dihydrate was 7–8 wt.%, and at 130 °C fluidization occurred [ 12 ]. This behavior is pretty similar to the one that has been reported recently for silybin [ 14 ], thus, this effect in quercetin dihydrate seems to be a thermochemical transition. The quercetin used in the current study is not the dihydrate form and exhibits a much lower mass loss (0.9 ± 0.3 wt.%) around 100 °C (these values were calculated from three independent repetitions of the TGA measurements).…”
Section: Resultssupporting
confidence: 89%
“…However, this is not always the case, e.g., for gallic acid [ 15 ]. Besides these factors, the absence of mass loss after this first minor decomposition step for a broad temperature range (e.g., for silybin, no mass loss has been detected in the range 180–260 °C [ 14 ], or for quercetin as presented in the current study) also contributes to the confusion regarding the phase behavior of flavonoids and other pharmaceuticals. Regarding modelling and the difficulty in the prediction of the thermodynamic properties of such molecules, it can be concluded that besides the structure and intermolecular interactions, the strength of chemical bonds and their weakening due to various factors should be taken into account.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Almost simultaneously with the above mentioned studies regarding polymers, the thermochemical transition was also reported to occur in some low molecular weight substances, namely two flavonoids (silybin [ 15 ] and quercetin [ 16 ]) and gallic acid [ 17 ]. It was reported [ 16 ] that the thermochemical transition is the “connection” among three different aspects [ 16 ].…”
Section: Introductionmentioning
confidence: 93%